Adequacy of damages - Stackpoole, C (2020)
Rheumatoid arthritis (RA) is a chronic inflammatory joint disease whose molecular pathogenesis serves as a useful model for understanding other chronic inflammatory conditions. Activated macrophages are critical for RA pathogenesis, since they promote the inflammation that causes cartilage damage, bone remodelling, pain and irreversible disability. Macrophages are activated by stimuli in their environment, and responses to these stimuli are fine-tuned by their interactions with highly sulfated heparan sulfate (HS) glycosaminoglycans. HS is sulfated in complex patterns, but 6-O-sulfation of HS glucosamine subunits is known to be particularly important for regulating activity of many cytokines, chemokines and growth factors. 6-O-sulfation is hence tightly regulated, and it is the only HS sulfation motif that can be post-synthetically removed by the extracellular sulfatases SULF1 and SULF2. Although extensively studied in cancer and development, the effect of 6-O-sulfation on inflammation and macrophage function is unknown.